Canadian Annual Review of Politics and Public Affairs 1978 - Byers, R. B.; Saywell, John T., 1929-2011 (Book collections on Project MUSE., 1980)
The book offers both a concise, convenient record of the year's events and a responsible appraisal of these important developments.